Ações do programa saúde na escola em município da região Oeste do Paraná - Mello, Manoela Aparecida Fumagalli Coelho (2018)
The School Health Program was established by Presidential Decree No 6,286 issued on December 5th, 2007, which aims to organize and implement health care for school children through health promotion actions and prevention of oncoming diseases based on strategies agreed between educators and health professionals who have searched for the development of intersectoral actions that may boost practices concerning the integral development and facing any vulnerabilities that may affect the development of these individuals. This program is based on three components: in component I, actions regarding the evaluation of the health conditions of the students are developed. Further, in component II, actions about health promotion and disease prevention are dealt with and lastly there is component III, which concerns training manager and the health and education staff that has conducted the program. The main question of this term paper intends to uncover the actions carried out by the School Health Program in a city located on the West of Paraná in the year of 2015 presenting the health diagnosis of the school population, the actions dealing with health promotion, the prevention of injuries and the specific training for action in this program.As for the specific objectives, these would achieve the overall goal: 1. to identify the actions developed by the School Health Program; 2. to describe health problems that have been found throughout evaluations; 3. to identify activities to promote health and prevent severe diseases; 4. to describe the measures taken in order to prepare the individuals involved in the program. For the development of this research, a descriptive study with a quantitative approach has been conducted. The research was carried out in the City of Cascavel-PR and it was led according to the data obtained by the School Health Program in 2015, therefore accessed in the database of the Municipal Health Department, where the corresponding actions for component I and the Simec website, which shares information related to components II and III, are registered. As stated in the data provided by SESAU, city of Cascavel, 28.930 students agreed to be assisted by activities related to component I. It has been shown that 24,084 out of these went through health assessments. Regarding nutritional diagnosis, Cascavel presented that 1.33% of the individuals were underweight, 4.49% were considerably underweight, 70.73% of the individuals were eutrophic, 21.64% were overweight and 1.75% of the data were not sampled. In relation to oral health, the municipal index of oral alterations was on 36.88%. Regarding eye health, 12.81% of the students had vision problems. As we analyze the results of component II, the mandatory subjects to be worked on health promotion have been offered to more than 90% of the students involved in the research. It has been confirmed that the actions related to component III were not carried out or were not registered in the Simec website. Thus, there is a need for measures to promote health and prevent diseases, so that the rates of change may decrease. Hence, it is suggested that the school health policy would be expanded in order to reach higher numbers of schoolchildren. Finally, especially important will be the investment in training and training for the program, and these should be planned and executed with the expectation that the program will reach its objectives and will effectively be applied.